Severe childhood SMA and axonal CMT due to anticodon binding domain mutations in the GARS gene. - James, P; Cader, M; Muntoni, F; Childs, A; Crow, Y; Talbot, K (2006)
We screened 100 patients with inherited and sporadic lower motor neuron degeneration and identified three novel missense mutations in the glycyl-tRNA synthetase (GARS) gene. One mutation was in the anticodon binding domain and associated with onset in early childhood and predominant involvement of the lower limbs, thus extending the phenotype associated with GARS mutations.